Depth of winter [compact disc, unabridged] - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery (Recorded Books, LLC), 2018)
Welcome to Walt Longmire's worst nightmare. In Craig Johnson's latest mystery, Depth of Winter, an international hit man and the head of one of the most vicious drug cartels in Mexico has kidnapped Walt's beloved daughter, Cady, to auction her off to his worst enemies, of which there are many. The American government is of limited help and the Mexican one even less. Walt heads into the one-hundred-and-ten degree heat of the Northern Mexican desert alone, one man against an army.